2021
DOI: 10.1002/chem.202004878
|View full text |Cite
|
Sign up to set email alerts
|

An Aldehyde Responsive, Cleavable Linker for Glucose Responsive Insulins

Abstract: A glucose responsive insulin (GRI) that responds to changes in blood glucose concentrations has remained an elusive goal. Here we describe the development of glucose cleavable linkers based on hydrazone and thiazolidine structures. We developed linkers with low levels of spontaneous hydrolysis but increased level of hydrolysis with rising concentrations of glucose, which demonstrated their glucose responsiveness in vitro. Lipidated hydrazones and thiazolidines were conjugated to the LysB29 side‐chain of HI by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…4) [114]. In the same study [114], in glucose clamp models, some insulin analogues demonstrated GRI activity, but their in vitro hydrolysis rates were >6 h, suggesting that lag time might be an issue.…”
Section: Intrinsic Gri Systemsmentioning
confidence: 88%
See 4 more Smart Citations
“…4) [114]. In the same study [114], in glucose clamp models, some insulin analogues demonstrated GRI activity, but their in vitro hydrolysis rates were >6 h, suggesting that lag time might be an issue.…”
Section: Intrinsic Gri Systemsmentioning
confidence: 88%
“…The strategy biased for glucose reactivity over fructose by virtue of aldehyde capture based on the increased reactivity of acyclic glucosyl aldehyde over fructosyl ketone and the fact that fasting glucose concentrations are about >1000-fold greater than those of fructose (Fig. 4) [114]. In the same study [114], in glucose clamp models, some insulin analogues demonstrated GRI activity, but their in vitro hydrolysis rates were >6 h, suggesting that lag time might be an issue.…”
Section: Intrinsic Gri Systemsmentioning
confidence: 93%
See 3 more Smart Citations